A Widely Used Drug Ulli (Palandu- Allium Cepa Linn) and its Formulations in Postnatal Care in Kerala, India - PK Beena Rose; Anita K Patel; K V Asha (International Journal of Ayurveda and Pharma Research, 2022)
In India, traditional postnatal care (PNC) has been practiced since ancient times. Traditional postnatal care practices by elder members from the family and the birth attendants are managed postnatal women with herbal home remedies as food and medicine. These formulations are recommended as single drug or compound preparations aiming at the objectives of PNC. The majority of the herbal formulations are given as Kwatha (decoctions), Lehya, Kalka (ground form), Kurukkumarunnu (porridge and powder) form. This paper is mainly concentrated on highlighting a traditional formulation with Cheriya Ulli - Palandu (Allium cepa Linn) in Sutika paricharya (post-natal care). Ayurvedic Samhitas, Nighantus, textbooks on Ethnomedicine, Internet publications and interviews with traditional birth attendants and Vaidyas are also were used to compile the relevant information and highlights the necessity to revive the age-old tradition of postnatal care that existed in Kerala. The present study reveals the prevalence of traditional PNC across Kerala through a cross-sectional study.